Clinical and laboratory characteristics but not response to treatment can distinguish children with definite growth hormone deficiency from short stature unresponsive to stimulation tests - Lanzetta, Maria Andrea; Dalla Bona, Eva; Tamaro, Gianluca; Vidonis, Viviana; Vittori, Giada; Faleschini, Elena; Barbi, Egidio; Tornese, Gianluca (Frontiers in Endocrinology, 2024)
Introduction: It has been proposed that not all children with short stature displaying an inadequate response to tests for growth hormone (GH) secretion truly suffer from GH deficiency (GHD). Only children with a monogenic cause of GHD or an identifiable combined hormonal deficiency or anatomical anomaly in the hypothalamic-pituitary axis should be considered definite GHD (dGHD). The remaining patients can be defined as a separate group of patients, "short stature unresponsive to stimulation tests" (SUS). The aim of this proof-of-concept study, was to assess whether SUS patients treated with rhGH exhibit any differences compared to GHD patients undergoing the same treatment.Methods: Retrospective analysis on 153 consecutive patients with GHD. Patients with dGHD were defined as those with a clear genetic or anatomical hypothalamic-pituitary anomaly (n=38, 25%); those without any of the previous anomalies were defined as SUS (n=115, 75%).Results: At diagnosis, dGHD and SUS populations did not differ significantly in sex, age, height SDS at diagnosis and prevalence of short stature (height <-2 SDS). IGF-1 SDS were significantly lower in dGHD (-2.0 vs -1.3, p<0.01). After 1 year of treatment, the prevalence of short stature was significantly reduced in both groups (31% in dGHD vs. 21% in SUS, p<0.01) without any significant differences between groups, while the increase in IGF-1 SDS for bone age was greater in the dGHD category (+1.9 vs. +1.5, p<0.01), with no further difference in IGF-1 SDS between groups. At the last available follow-up, 59 patients had reached the near adult height (NAH) and underwent retesting for GHD. No differences in NAH were found. The prevalence of pathological retesting was higher in dGHD (60% vs. 10%, p<0.01) as well as overweight and obesity (67% vs. 26%). Conclusion: Stimulation tests and the equivalent benefit from rhGH therapy, cannot distinguish between dGHD and SUS populations. In addition, lower IGF-1 concentrations at baseline and their higher increase during treatment in dGHD patients, and the lack of pathological retesting upon reaching NAH in SUS patients, are facts that suggest that deficient GH secretion may not be the cause of short stature in the SUS studied population.